Identification of Enterobacteriaceae in the Clinical Microbiology Laboratory - Traub, Walter H. (1970)
A total of 5,137 enterobacterial clinical isolates were examined with three series of biochemical tests. The data were analyzed with respect to the use of economical and practical procedures for the accurate identification of lactose-fermenting and -nonfermenting Enterobacteriaceae within 24 hr after isolation.